2000
DOI: 10.1021/jm990179s
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal Affinity Labels of the Estrogen Receptor α. 4. Electrophilic 11β-Aryl Derivatives of Estradiol

Abstract: Ten electrophilic estradiol 11beta-aryl derivatives were synthesized, with three different types of 11beta-substituent: (i) pOO(CH(2))(2)X (compounds: 6, X = OSO(2)CH(3); 7, X = I; 13, X = NHCOCH(2)Cl; 15, X = N(CH(3))COCH(2)Br; and 16, X = N(CH(3))COCH(2)Cl); (ii) pOO(CH(2))(5)X (compounds: 17, X = I; 20, X = NHCOCH(2)Br; and 22, X = N(CH(3))COCH(2)Br); and (iii) pOC(triple bond)CCH(2)X (compounds: 27, X = NHCOCH(2)Cl; and 29, X = N(CH(3))COCH(2)Cl). The range of their apparent affinity constants for binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…In this study, the Cys 530 S of human ER␣ LBD was identified as the quasi-exclusive (11BAEOPE 2 ) or main (11BAPOPE 2 ) covalent attachment site of 11BAEOPE 2 and 11BAPOPE 2 , two potent and high affinity antiestrogens [16]. Cys 530 was previously found to be the covalent attachment site of low affinity non-steroidal electrophiles, ketononestrol aziridine, a diphenylethane estrogen and tamoxifen aziridine, a triphenylethylene antiestrogen [22], whereas by means of an indirect approach based on the use of various Cys → Ala ER␣ mutants [17], Cys 530 appeared to be involved in the covalent attachment of E 2 11␤-aziridinylalkoxyphenyl derivatives (two compounds, related to 11BAEOPE 2 and 11BAPOPE 2 ) [18].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this study, the Cys 530 S of human ER␣ LBD was identified as the quasi-exclusive (11BAEOPE 2 ) or main (11BAPOPE 2 ) covalent attachment site of 11BAEOPE 2 and 11BAPOPE 2 , two potent and high affinity antiestrogens [16]. Cys 530 was previously found to be the covalent attachment site of low affinity non-steroidal electrophiles, ketononestrol aziridine, a diphenylethane estrogen and tamoxifen aziridine, a triphenylethylene antiestrogen [22], whereas by means of an indirect approach based on the use of various Cys → Ala ER␣ mutants [17], Cys 530 appeared to be involved in the covalent attachment of E 2 11␤-aziridinylalkoxyphenyl derivatives (two compounds, related to 11BAEOPE 2 and 11BAPOPE 2 ) [18].…”
Section: Discussionmentioning
confidence: 94%
“…Trypsin (sequencing grade) was from Promega, and ␣-cyano-4-hydroxycinnamic acid was from Sigma-Aldrich. Unlabeled 11BAEOPE 2 and 11BAPOPE 2 had been previously synthesized [16]. Solvents and compounds used for HPLC and electrospray ionization (ESI) and matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) MS analyses were HPLC grade (for HPLC, Millipore Q water was passed through a C18 preparative column and then sterilized).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an electrostatic interaction involving the methyl group at C (13) and the oxygen atom at C (11) could take place when the hydroxyl group is in the axial orientation ([III ␤ -H] Ϫ ). This interaction is reinforced by the steric repulsion occur- ⌬E ϭ E considered structure Ϫ E of the most stable structure .…”
Section: Gas-phase Acidity Of the Steroidsmentioning
confidence: 99%
“…The E 2 /ER␣ complex is stabilized by hydrogen contacts occurring between, on the one hand, the hydroxyl group of phenolic A ring (E 2 ) and Glu-353 as well as Arg-394 of the hormone binding pocket (HBP), and on the other hand, between the 17␤-hydroxyl of D-ring and His-524 (Scheme 1a) [5][6][7]. Moreover, position around the functionalized site at the C (11) position (C ring) seems to contribute to the anchorage of the hormone within this pocket of the receptor [7][8][9][10][11][12][13], suggesting that steric effects at this position are important for binding affinity. Accordingly, we may consider that the proton donor character efficiency could be reinforced through electrostatic effects mediated by the nature and the stereochemistry of substituent in position 11 [14].…”
mentioning
confidence: 99%